PENGEMBANGAN KURIKULUM 2013 (Studi Analitis dan Subtantif Kebijakan Kurikulum Nasional) - SUBANDI, SUBANDI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
The last curriculum change was in 2006 known as the School-based Curriculum (SBC). The implementation of SBC is not optimal due to various factors, including the teachers’s competence and facilities and also infrastructure are still limited , and the scoring system is still weak. Substitution successive curriculum has not been able to improve the quality of education national. The essential change in the implementation of curriculum 2013 are: learning approach using sciencetific approach, (observing, asking, trying, reasoning and making networking ). The structure of the curriculum starts from the analysis of graduate competency standards (SKL), then determine the core competencies (KI.1 , KI 2 , 3 and KI KI 4), KI 1, containing the competencies of (religious) to the sublime monotheism creator, KI 2, contains competencies about the relationship of humanity (human relationship), KI 3, contains competencies of Science (knowledge), KI 4 contains the competencies skills (skills), the implementation of learning academic subjects evolved into an integrated and thematic integrated curriculum especially in elementary school. Initially, assessment based on results in Curriculum 2013 put forward a process than the result through portofolio with authentic assessment in which the affective, cognitive and psychomotor assessed simultaneously.